A Proposed pre-retirement education program for retiring public elementary school teachers in the City of San Fernando, La Union - Hidalgo, Rizalyn P. (University of Pangasinan : [s.n.], 2019)
This study entitled "A Proposed Pre-Retirement Education Program for Retiring Public Elementary School Teachers in the City of San Fernando, La Union" - aimed to propose a pre-retirement education program for retiring public elementary school teachers in the City of San Fernando, La Union. The proposed pre-retirement education program was crafted after a determination of the: profile of the retired teachers in terms of physical well-being. mental well-being, social well-being, financial well-being, and productivity: identification of the challenges encountered by the retired teachers; and, identification of the strategies used by the retired teachers to cope up with the challenges. The writer hopes that, through this program, teachers will be prepared in entering the retirement life.
Bibliography: pages 122-128.
CHEd-La Uniion
Keywords: Retirement -- Teachers